Dynamic Globalization and its Potentially Alarming Prospects for Low-Wage Workers - Hans Fehr; Sabine Jokisch; Laurence J. Kotlikoff (FIW - Research Centre International Economics, 2009)
Will incomes of low and high skilled workers continue to diverge? Yes says our paper's dynamic, six-good, five-region - U.S., Europe, N.E. Asia (Japan, Korea, Taiwan, Hong Kong), China, and India -, general equilibrium, life-cycle model. The model predicts a near doubling of the ratio of high- to low-skilled wages over the century. Increasing wage inequality arises from a traditional source - a rising worldwide relative supply of unskilled labor, reflecting Chinese and Indian productivity improvements. But China's and India's education policies matter. If successive Chinese and Indian cohorts become more skilled, major exacerbation of inequality will be precluded.
Keywords: 330; Demographic transition; overlapping generations (OLG); computable general equilibrium models (CGE)